A study on compatibility of polymer blends of Poly(2,6-dimethyl-1,4-phenyleneoxide)/Poly(ether imide) - Cakar, F.; Yazici, O.; Cankurtaran, O.; Karaman, F. (NATL INST OPTOELECTRONICS, 2012)
The miscibility criteria of poly (2,6-dimethyl-1,4-phenylene oxide) (PPO) and poly(ether imide) (Ultem) were investigated at 30 degrees C in chloroform in dilute solutions by viscometric analysis. The intrinsic viscosity and viscometric parameters of this blend system were determined for several PPO/Ultem mixtures in compositions such as 80/20, 60/40, 40/60, 10/90 in chloroform solutions. The miscibility criteria on the basis of the sign of the parameters Delta b(m), Delta b'(m), Delta[eta](m) and beta proposed by Krigbaum and Wall, Catsiff and Hewett, Garcia et al. and Jiang and Han, respectively, which are the difference between their experimental and ideal values were calculated by applying theoretical equations. The data obtained from the viscometry studies suggested that the prepared blends were partially miscible in all of the studied composition ranges at 30 degrees C. The miscibility of the mixtures was also studied by Fourier transform infrared spectroscopy.
Keywords: Poly (2,6-dimethyl-1,4-phenylene oxide); Poly(ether imide); Miscibility; Viscometry; FTIR; DILUTE-SOLUTIONS; BISPHENOL-A; OXIDE); COPOLYESTER; TRANSITIONS; PPO; Materials Science; Optics